2003
DOI: 10.1111/j.1440-1819.2004.01191.x
|View full text |Cite
|
Sign up to set email alerts
|

Three‐year follow up of women with and without borderline personality disorder: development of Cloninger's character in adolescence

Abstract: The purpose of the present study was to examine the developmental patterns of Cloninger's biogenetic character traits in subjects with borderline personality disorder (BPD). Study subjects met Diagnostic and Statistical Manual of Mental Disorders (3rd edn, revised; DSM-III-R) criteria for BPD without comorbid axis I or II disorders, as determined by the Diagnostic Interview for Borderlines-Revised, Structured Clinical Interview for the DSM-III-R, and Diagnostic Interview for Personality Disorders. The BPD subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…However, the biosocial model might contribute to the identification of the moderators and mediators for therapy effects. For example, a long-term longitudinal study examining the differences in the developmental character pattern in BPD and healthy comparison subjects found that BPD subjects had little change of selfdirectedness-related maturity with increasing age, while healthy subjects became more responsible, goal-oriented and effective in personality development with age [28] . The results of an another longitudinal study indicate that there is a specific temporal relationship between traits and PDs, whereby changes in the personality traits lead to subsequent changes in the disorder [60] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the biosocial model might contribute to the identification of the moderators and mediators for therapy effects. For example, a long-term longitudinal study examining the differences in the developmental character pattern in BPD and healthy comparison subjects found that BPD subjects had little change of selfdirectedness-related maturity with increasing age, while healthy subjects became more responsible, goal-oriented and effective in personality development with age [28] . The results of an another longitudinal study indicate that there is a specific temporal relationship between traits and PDs, whereby changes in the personality traits lead to subsequent changes in the disorder [60] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, while several studies have reported that impulsiveness-related traits (e.g. novelty seeking) are among the core features of BPD pathology [26][27][28] , others have not found increased scores for measures of novelty seeking among subjects with BPD [29,30] . These inconsistencies might result from at least 3 issues.…”
mentioning
confidence: 99%